Pendampingan Keluarga Dan Pasien Gangguan Autoimun Dalam Perawatan Di Rumah Dan Upaya Peningkatan Kualitas Hidup : Pendampingan Keluarga dan Pasien Gangguan Autoimun dalam Perawatan di Rumah dan Upaya Peningkatan Kualitas Hidup - Dian Wahyuni; Hikayati; Eka Yulia Fitri; Dhona Andhini (Universitas Muhammadiyah Palembang, 2025)
This activity conducted to evaluate the effect of mentoring on patient and family knowledge regarding complementary therapies to improve the quality of life of patients with Systemic Lupus Erythematosus (SLE). The mentoring method includes health checkups, storytelling experiences by Odapus, and education through lectures and the use of booklets. This program done by used three methods: (1) urine examination while using a urine dipstick, (2) health education about complementary therapy through lectures and booklets, and (3) experience sharing sessions by SLE patients and their families about dealing with disease recurrence. Data were also collected for thesis purposes. The number of participants exceeded the target (>30 people). Participants (patients and families) voluntarily shared their experiences of caring and their state of quality of life. Pre-test and post-test show a significant increase in knowledge. Participants reported positive results from sharing experiences and improving quality of life. PLSS members are committed to continuing mentoring programs with other topics. This activity successfully increased the knowledge of patients and their families. Participants requested the continuation of the support program, specifically suggesting health check-ups including Hb level tests and ongoing education regarding the positive and negative impacts of complementary therapies.